The Teacher Role Guiding Students Entering Higher Education - Kusmiarso Kusmiarso; Suryadi Suryadi; Siti Zulaikha (AL-ISHLAH: Jurnal Pendidikan, 2021)
The uptake of students in state universities is the responsibility of teachers and schools in guiding them. Therefore, the purpose of the study was to find information related to teacher guidance for students to enter college. The research approach is qualitative through a survey. Data were collected through interviews, documents, and questionnaires. The data analysis process includes data collection, data reduction, data display, and conclusion. The results showed that the data on student absorption in higher education during the last two years had increased. It provides an overview of the leading role of teachers in guiding students to enter college. From the questionnaire data, it can be seen that the data results support the increase in the number of students entering higher education. The results of this study can also be used as a reference for schools in developing guidance programs for students entering college.